Historical and Contemporary Geopolitical Tendencies of the Great Powers With Special Reference to the Security of the Republic of Serbia - Mirković, Vladan M; Stajić, Ljubomir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Geopolitics explains the regularity of political action in international relations by finding the determinants of political decisions in geographical factors. The result of geopolitical thought are possible patterns of behavior of states in international relations which are used to explain past and present and predict future events. Starting from the basic principles of Mackinder’s and Spykman’s theory, the paper presents the historical and contemporary geopolitical tendencies of the Great Powers in Europe, with special reference to the territory where the modern Serbian state is located. At the end, we identified indicators of future development of the geopolitical situation with implications for the security of the Republic of Serbia could be predicted.